2016
DOI: 10.1111/ped.12915
|View full text |Cite
|
Sign up to set email alerts
|

Early predictive echocardiographic features of hemodynamically significant patent ductus arteriosus in preterm VLBW infants

Abstract: Echocardiographic features such as short ductal length and short or absent ductal constriction area can be used to predict hsPDA for early decision making strategies in VLBW preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…Results have showed that LA/Ao is delayed in proving hemodynamic significance of PDA. This is in agreement with previous studies that though it is easy to perform, its accuracy in predicting hemodynamic significance of PDA is low [14].…”
Section: Discussionsupporting
confidence: 92%
“…Results have showed that LA/Ao is delayed in proving hemodynamic significance of PDA. This is in agreement with previous studies that though it is easy to perform, its accuracy in predicting hemodynamic significance of PDA is low [14].…”
Section: Discussionsupporting
confidence: 92%
“…Our data suggest that small gestational age may be an important risk factor for PDA outcome, which is consistent with the conclusions of previously studies [9,14]. Although no differences in birth weight were observed between groups, the correlation analysis showed that a lower birth weight was associated with smaller IT2 and Va values.…”
Section: Discussionsupporting
confidence: 92%
“…Eleven different articles were included in group 1 which contained preterm infants with a gestational age under 28 weeks and/or birth weight under 1,000 g ( 15 20 , 54 , 63 66 ). The median of reported mean or median GAs of the 17,156 patients in group 1 was 26.0 (range of mean/median 25.5–26.6) weeks.…”
Section: Resultsmentioning
confidence: 99%